High-element doped optical fiber with stable attenuation and preparation method thereof

By adjusting the density distribution of the deposited loose medium of the high-element doped fiber core rod, the problem of increasing short wavelength attenuation of the fiber after deuterium gas treatment is solved, and the stability of the fiber attenuation is improved.

CN119689632AActive Publication Date: 2025-03-25HENGTONG OPTICAL MATERIAL CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411888631.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

After the deuterium treatment of high-element doped fiber, the attenuation of the short-wavelength band increases significantly, while the attenuation of the long-wavelength band basically does not change, resulting in a decline in fiber performance.

Method used

By monitoring and adjusting the density distribution of the deposition loose material of the core rod, controlling the density distribution and thickness of each layer of the deposition loose material, reducing the occurrence of interrupted bond defects during subsequent deformation, thereby reducing the attenuation of the optical fiber after deuterium gas treatment.

Benefits of technology

After deuterium gas treatment, the attenuation increase of the 1310nm and 1383nm bands is less than 0.02dB/km, and the attenuation of the 1550nm band does not change, which significantly improves the attenuation stability of the optical fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119689632A_ABST
    Figure CN119689632A_ABST
Patent Text Reader

Abstract

The invention discloses a high-element-doped optical fiber with stable attenuation. The high-element-doped optical fiber comprises a core rod, a sunken cladding layer and an outer cladding layer, the core rod is prepared by sintering, degassing and stretching a deposition loose body prepared by a vapor deposition process; wherein the deposition loose body comprises a core layer, a soft layer, a core-cladding combination layer, a cladding layer I and a cladding layer II which are sequentially arranged from inside to outside; the thickness of the core-cladding bonding layer is 0-3mm, the thickness of the soft layer is 0-2mm, and the density distribution of each layer of the deposited loose body meets the following conditions: rho core layer lt; the Rho cladding 1, the Rho core layer is greater than or equal to the Rho cladding 2, the Rho max-Rho core-cladding bonding layer is less than the Rho max-Rho cladding 1, and the Rho max is the maximum deposition density of the deposition loose body. By controlling the density distribution and the thickness of the deposited loose body, the generation of broken bond defects in the subsequent deformation process is reduced, and the purpose of reducing optical fiber attenuation after deuterium gas treatment can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optical fiber technology, and in particular to a highly element-doped optical fiber with stable attenuation and a preparation method thereof. Background Art

[0002] In some special optical fibers, such as optical fibers with high doping of certain elements, a phenomenon is likely to occur during the attenuation test after drawing: the attenuation of the 1310nm, 1383nm and 1550nm bands of the large optical fiber disk is normal, but after the optical fiber is treated with deuterium, the attenuation of the short wavelength 1310nm and 1383nm of the small disk test increases significantly, and the attenuation of the long wavelength 1550nm basically does not change. The reason for this phenomenon may be that the peroxide bond -OO- or the chemical bond Ge-O-Ge, Si-O-Si, Si-O-Ge of the optical fiber preform itself shrinks and stretches, and breaks during the optical fiber drawing process to produce defects (non-bridging oxygen hollow defect (NBOHC), E' center defect, peroxyl radical, etc.). During the deuterium treatment process, if the defect concentration reaches a certain level, the deuterium molecules will form a relatively strong bond with the defects. At this time, some deuterium molecules will remain in the optical fiber, causing the short wavelength attenuation to increase.

[0003] Highly doped optical fiber products, such as G657.A2 optical fiber, are prone to forming weaker chemical bonds due to the large amount of specific element doping. The probability of bond breaking and thus defects is high, and the attenuation is prone to increase. Similarly, some products with complex production process paths undergo multiple and repeated stretching during the production and preparation process, and the chemical bonds are easily damaged, resulting in the above phenomenon.

[0004] Traditional methods to improve the increased attenuation of optical fiber after deuterium treatment, on the one hand, mainly focus on reducing the peroxide bonds in the core layer of the optical fiber preform. Since the peroxide group is easy to break and form defects, it is necessary to regulate the sintering atmosphere and control the amount of helium, oxygen and chlorine. This method has been proven to be effective, but a balance point must be reached, otherwise the three defects: non-bridging oxygen hollow defects (NBOHC), E' center defects, peroxide free radicals, etc. may appear to increase and decrease, and still affect the optical fiber attenuation; on the other hand, it mainly starts from the control of drawing speed, cooling method and drawing tension, but reducing the drawing speed and adding annealing furnaces will affect the optical fiber production capacity and drawing cost, and there are certain disadvantages.

[0005] Chinese patent CN108751750A provides a method for stabilizing optical fiber attenuation by adding a nitrogen heating treatment process after the optical fiber is treated with deuterium gas, so that the excess deuterium molecules inside the optical fiber treated with deuterium gas can be effectively released by heating to stabilize the optical fiber attenuation. In this way, most of the additional attenuation can be removed, but a small part of the additional attenuation (about 0.003dB / km@1310nm) will still remain because the deuterium gas forms a strong bond with the defects and cannot be removed. On the one hand, the small part of the additional attenuation that cannot be removed will also have a certain impact on the relevant performance of the optical fiber. On the other hand, adding a nitrogen heat treatment process also prolongs the circulation cycle of optical fiber products, making on-site control more difficult and increasing costs. Summary of the invention

[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a highly element-doped optical fiber with stable attenuation and a preparation method thereof. The present invention can reduce the attenuation of the optical fiber after deuterium treatment by monitoring and adjusting the density distribution of the deposited loose body of the core rod, controlling the density distribution and thickness of the deposited loose body, and reducing the generation of broken bond defects in the subsequent deformation process.

[0007] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0008] On one hand, the present invention provides a highly element-doped optical fiber with stable attenuation, comprising a core rod, a depressed cladding and an outer cladding; the core rod is made of a deposited loose body made by a vapor deposition process through sintering, degassing and stretching processes; wherein the deposited loose body comprises a core layer, a soft layer, a core-cladding bonding layer, a cladding layer 1 and a cladding layer 2 arranged in sequence from the inside to the outside, the thickness of the core-cladding bonding layer is 0 to 3 mm, and the thickness of the soft layer is 0 to 2 mm; the density distribution of each layer of the deposited loose body meets the following conditions: the densities of the core layer, the core-cladding bonding layer, the cladding layer 1 and the cladding layer 2 are respectively expressed as ρ 芯层 , 芯包结合层 , 包层一 , 包层二 , ρ 芯层 < 包层一 , ρ 芯层 ≥ρ 包层二 , ρ max ﹣ρ 芯包结合层 ﹤ρ max ﹣ρ 包层一 , where ρ max is the maximum sedimentary density of the sedimentary loose body.

[0009] Furthermore, the overall density of the deposited loose body is 0.200-0.400 g / cm 3 .

[0010] Furthermore, the deposited loose body is deposited by axial vapor deposition or out-of-tube vapor deposition process.

[0011] Furthermore, the sunken cladding is formed by melting and shrinking through a sleeve method.

[0012] Furthermore, the outer cladding is deposited by an OVD deposition process.

[0013] Furthermore, the core rod comprises a core layer and an inner cladding according to the refractive index distribution, wherein the inner cladding is made of a soft layer of deposited loose body, a core-cladding bonding layer, cladding one and cladding two.

[0014] Furthermore, the core layer is doped with germanium or germanium and chlorine, and its refractive index is 0.0040 to 0.0060, the inner cladding is doped with fluorine, and its refractive index is -0.0004 to -0.0020, the depressed cladding is doped with fluorine, and its refractive index is between -0.0060 and -0.0030, and the outer cladding is a pure silicon layer with a refractive index of 0 to 0.0004.

[0015] Furthermore, the core rod has a core ratio of 2.2 to 3.0, the core ratio of the sunken cladding to the core layer is 3.8 to 5.5, and the core ratio of the outer cladding to the core layer is 14 to 20.

[0016] Furthermore, after the attenuation-stable high-element-doped optical fiber is treated with deuterium gas, the attenuation increases in the 1310nm and 1383nm bands are both less than 0.02dB / km, and the attenuation in the 1550nm band remains unchanged.

[0017] Another aspect of the present invention provides a method for preparing a highly element-doped optical fiber with stable attenuation, comprising the following steps:

[0018] (1) The deposition loose body is made by the vapor deposition process. During the deposition process, the amount of fuel gas is controlled so that the density distribution of each layer of the formed deposition loose body meets the following conditions: the density of the core layer, the core-clad bonding layer, the cladding layer 1 and the cladding layer 2 are respectively expressed as ρ 芯层 , 芯包结合层 , 包层一 , 包层二 , ρ 芯层 < 包层一 , ρ 芯层 ≥ρ 包层二 , ρ max ﹣ρ 芯包结合层 ﹤ρ max ﹣ρ 包层一 , where ρ max is the maximum sedimentary density of the sedimentary loose body;

[0019] (2) forming a core rod by sintering, degassing and stretching the deposited loose body;

[0020] (3) preparing a depressed cladding outside the core rod, preparing an outer cladding outside the depressed cladding, and then sintering to form an optical fiber preform;

[0021] (4) The optical fiber preform obtained in step (3) is drawn into the attenuation-stable high-element-doped optical fiber.

[0022] The beneficial effects of the present invention are:

[0023] The present invention controls the density distribution of the deposited loose body by monitoring and adjusting the density distribution of the deposited loose body on the core rod to meet the following conditions: 芯层 < 包层一 , ρ 芯层 ≥ρ 包层二 , ρ max ﹣ρ 芯包结合层 ﹤ρ max ﹣ρ 包层一 , and control the thickness of the deposited loose body to reduce the generation of broken bond defects in the subsequent deformation process, so as to achieve the purpose of reducing the attenuation of the optical fiber after deuterium treatment;

[0024] The present invention also controls the refractive index profile distribution of each layer to form a certain refractive index gradient between the sunken cladding and the inner cladding and the outer cladding, optimizes the stress distribution, achieves viscosity matching, reduces the stress on the core layer during the drawing process, reduces core layer defects and achieves the purpose of reducing post-deuterium attenuation.

[0025] After the attenuation-stable high-element-doped optical fiber is treated with deuterium gas, the attenuation increases of the 1310nm and 1383nm bands are both less than 0.02dB / km, and the attenuation of the 1550nm band remains unchanged. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a density curve diagram of the deposited loose body according to an embodiment of the present invention.

[0027] Figure 2 This is a density curve of the deposited loose body of the comparative example. DETAILED DESCRIPTION

[0028] The technical solutions in the present invention will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] On one hand, the present invention provides a highly element-doped optical fiber with stable attenuation, comprising a core rod, a depressed cladding and an outer cladding; the core rod is made of a deposited loose body made by a vapor deposition process and then sintered, degassed and stretched; wherein the deposited loose body comprises a core layer, a soft layer, a core-cladding bonding layer, a cladding one and a cladding two arranged in sequence from the inside to the outside; the thickness of the core-cladding bonding layer is 0 to 3 mm, the thickness of the soft layer is 0 to 2 mm, and the thickness of the loose bodies of the remaining core layers and claddings varies depending on different products and cladding-core ratios; the density distribution of each layer of the deposited loose body satisfies the following conditions: the densities of the core layer, the core-cladding bonding layer, the cladding one and the cladding two are respectively expressed as ρ 芯层 , 芯包结合层 , 包层一 , 包层二 , ρ 芯层 < 包层一 , ρ 芯层 ≥ρ 包层二 , ρ max ﹣ρ 芯包结合层 ﹤ρ max ﹣ρ 包层一 , where ρ max is the maximum sedimentary density of the sedimentary loose body.

[0030] The overall density of the deposited loose body is 0.200-0.400 g / cm 3 .

[0031] The deposited loose body is deposited by adopting an axial vapor deposition process or an out-of-tube vapor deposition process.

[0032] The sunken cladding is preferably formed by melting and shrinking through a sleeve method; and the outer cladding is preferably deposited through an OVD deposition process.

[0033] The core rod comprises a core layer and an inner cladding according to the refractive index distribution, wherein the inner cladding is made of a soft layer of deposited loose bodies, a core-cladding bonding layer, a cladding layer 1 and a cladding layer 2.

[0034] The core layer is doped with germanium or germanium and chlorine, and its refractive index is 0.0040 to 0.0060. The inner cladding is doped with fluorine, and its refractive index is -0.0004 to -0.0020. The depressed cladding is doped with fluorine, and its refractive index is between -0.0060 and -0.0030. The outer cladding is a pure silicon layer, and its refractive index is 0 to 0.0004.

[0035] The core rod has a core ratio of 2.2 to 3.0, the sunken cladding and the core layer have a core ratio of 3.8 to 6.0, and the outer cladding and the core layer have a core ratio of 14 to 20.

[0036] After deuterium treatment, the attenuation increase of the highly doped optical fiber in the 1310nm and 1383nm bands is less than 0.02dB / km, and the attenuation of the 1550nm band remains unchanged.

[0037] Another aspect of the present invention provides a method for preparing a highly element-doped optical fiber with stable attenuation, comprising the following steps:

[0038] (1) A deposition bulk body is formed by a vapor deposition process. Specifically, the deposition bulk body is obtained by gradually depositing a layer of "powder" produced by a flame hydrolysis reaction of gaseous halides (SiCl4, GeCl4, etc.) carried in a hydrogen-oxygen flame or a methane flame. During the deposition process, the amount of fuel gas is controlled so that the density distribution of each layer of the formed deposition bulk body meets the following conditions: the densities of the core layer, the core-clad bonding layer, the cladding layer 1 and the cladding layer 2 are respectively expressed as ρ 芯层 , 芯包结合层 , 包层一 , 包层二 , ρ 芯层 < 包层一 , ρ 芯层 ≥ρ 包层二 , ρ max ﹣ρ 芯包结合层 ﹤ρ max ﹣ρ 包层一 , where ρ max is the maximum sedimentary density in the sedimentary loose body;

[0039] (2) forming a core rod by sintering, degassing and stretching the deposited loose body;

[0040] (3) preparing a depressed cladding outside the core rod, preparing an outer cladding outside the depressed cladding, and then sintering to form an optical fiber preform; wherein the depressed cladding is preferably formed by melting and shrinking through a sleeve method, that is, a sleeve is sleeved outside the core rod and then melted and shrunk; the outer cladding is preferably deposited through an OVD deposition process.

[0041] (4) The optical fiber preform obtained in step (3) is drawn into the attenuation-stable high-element-doped optical fiber.

[0042] Example

[0043] The deposition loose body is prepared by VAD (axial vapor deposition) method, and then made into a core rod through sintering, degassing and stretching process. The RIC method (casing method) melts and shrinks the sunken cladding. The OVD method deposits the sunken cladding, and then sintered to make an optical fiber preform rod. The optical fiber preform rod is made into an optical fiber after drawing. Among them, the deposition loose body includes a core layer, a soft layer, a core-cladding bonding layer, a cladding layer 1 and a cladding layer 2 arranged from the inside to the outside in sequence; the core rod includes a core layer and an inner cladding layer according to the refractive index distribution; during the deposition process of the deposition loose body, by controlling the amount of fuel gas (H2 or CH4), the density distribution of each layer is as follows Figure 1 The density curve is obtained by industrial computer tomography, or by continuous measurement and calculation of the loose body weight obtained by a weighing sensor and the loose body diameter fed back by a laser diameter gauge.

[0044] The relevant parameters of the optical fiber of this embodiment are as follows: the refractive index of the core layer is 0.0055, the refractive index of the inner cladding is -0.0003, the refractive index of the depressed cladding is -0.0048, and the refractive index of the outer cladding is 0.0003; the core rod core ratio (the diameter ratio of the core layer and the inner cladding) is 2.47, the core ratio of the depressed cladding to the core layer is 5.18, and the core ratio of the outer cladding to the core layer is 17.9.

[0045] The density distribution of the deposited loose body of the core rod is shown in Figure 1 , wherein the thickness of the core package bonding layer is 0.78 mm, and the thickness of the soft layer is 0.59 mm.

[0046] The optical fiber of this embodiment is made by drawing process with auxiliary annealing process at 2000m / min speed. The optical fiber is tested for attenuation by PK8000. The attenuation of 1310nm band, 1383nm band and 1550nm band before and after deuterium treatment is shown in Table 1. The attenuation before and after deuterium treatment is relatively stable and the change is not large.

[0047] Table 1 Attenuation data before and after deuterium treatment in Example

[0048]

[0049] Comparative Example

[0050] The deposition loose body is prepared by VAD (axial vapor deposition) method, and then made into a core rod through sintering, degassing and stretching process. The RIC method (casing method) melts and shrinks the sunken cladding. The OVD method deposits the sunken cladding, and then sintered to make an optical fiber preform rod. The optical fiber preform rod is made into an optical fiber after drawing. Among them, the deposition loose body includes a core layer, a soft layer, a core-cladding bonding layer, a cladding layer 1 and a cladding layer 2 arranged from the inside to the outside in sequence; the core rod includes a core layer and an inner cladding layer according to the refractive index distribution; during the deposition process of the deposition loose body, by controlling the amount of fuel gas (H2 or CH4), the density distribution of each layer is as follows Figure 2 shown.

[0051] The relevant parameters of the optical fiber of this comparative example are as follows: the refractive index of the core layer is 0.0053, the refractive index of the inner cladding is -0.0004, the refractive index of the depressed cladding is -0.0049, and the refractive index of the outer cladding is 0.0003; the core rod core ratio (the diameter ratio of the core layer and the inner cladding) is 2.50, the core ratio of the depressed cladding to the core layer is 4.19, and the core ratio of the outer cladding to the core layer is 18.1.

[0052] The density distribution of the deposited loose body of the core rod is shown in Figure 2 , wherein the thickness of the core package bonding layer is 4.05 mm, and the thickness of the soft layer is 1.55 mm.

[0053] The optical fiber of this comparative example is made under the drawing process of 2000m / min speed and auxiliary annealing process. The optical fiber attenuation is tested by PK8000. The attenuation of 1310nm band, 1383nm band and 1550nm band before and after deuterium treatment is shown in Table 2. After deuterium treatment, the attenuation of 1310nm and 1383nm bands increases greatly, and the attenuation of 1550nm does not change significantly. The thickness of the core-clad bonding layer is large, which leads to the phenomenon of increased attenuation of the optical fiber after deuterium treatment.

[0054] Table 2 Attenuation data of comparative example before and after deuterium treatment

[0055]

[0056] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0057] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A highly element-doped optical fiber with stable attenuation, characterized in that: The invention comprises a core rod, a sunken cladding and an outer cladding; the core rod is made of a deposited loose body made by a vapor deposition process through sintering, degassing and stretching processes; wherein the deposited loose body comprises a core layer, a soft layer, a core-cladding bonding layer, a cladding layer 1 and a cladding layer 2 arranged in sequence from the inside to the outside, the thickness of the core-cladding bonding layer is 0 to 3 mm, and the thickness of the soft layer is 0 to 2 mm; the density distribution of each layer of the deposited loose body satisfies the following conditions: the density of the core layer, the core-cladding bonding layer, the cladding layer 1 and the cladding layer 2 are respectively expressed as ρ 芯层 , 芯包结合层 , 包层一 , 包层二 , ρ 芯层 < 包层一 , ρ 芯层 ≥ρ 包层二 , ρ max ﹣ρ 芯包结合层 ﹤ρ max ﹣ρ 包层一 , where ρ max is the maximum sedimentary density of the sedimentary loose body.

2. The attenuation-stable highly element-doped optical fiber according to claim 1, characterized in that: The overall density of the deposited loose body is 0.200-0.400 g / cm 3 .

3. The attenuation-stable highly element-doped optical fiber according to claim 1, characterized in that: The deposited loose body is deposited by adopting an axial vapor deposition process or an out-of-tube vapor deposition process.

4. The attenuation-stable highly element-doped optical fiber according to claim 1, characterized in that: The sunken cladding is formed by melting and shrinking through a casing method.

5. The attenuation-stable highly element-doped optical fiber according to claim 1, characterized in that: The outer cladding layer is deposited by an OVD deposition process.

6. The attenuation-stable highly element-doped optical fiber according to claim 1, characterized in that: The core rod comprises a core layer and an inner cladding according to the refractive index distribution, wherein the inner cladding is made of a soft layer of deposited loose bodies, a core-cladding bonding layer, a cladding layer 1 and a cladding layer 2.

7. The attenuation-stable highly element-doped optical fiber according to claim 6, characterized in that: The core layer is doped with germanium or germanium and chlorine, and its refractive index is 0.0040 to 0.0060. The inner cladding is doped with fluorine, and its refractive index is -0.0004 to -0.0020. The depressed cladding is doped with fluorine, and its refractive index is between -0.0060 and -0.0030. The outer cladding is a pure silicon layer, and its refractive index is 0 to 0.0004.

8. The attenuation-stable highly element-doped optical fiber according to claim 6, characterized in that: The core rod has a core ratio of 2.2 to 3.0, the core ratio of the sunken cladding to the core layer is 3.8 to 5.5, and the core ratio of the outer cladding to the core layer is 14 to 20.

9. The attenuation-stable highly element-doped optical fiber according to claim 1, characterized in that: After the attenuation-stable high-element-doped optical fiber is treated with deuterium gas, the attenuation increases of the 1310nm and 1383nm bands are both less than 0.02dB / km, and the attenuation of the 1550nm band remains unchanged.

10. A method for preparing a highly element-doped optical fiber with stable attenuation, characterized in that: The steps include: (1) The deposition loose body is made by the vapor deposition process. During the deposition process, the amount of fuel gas is controlled so that the density distribution of each layer of the formed deposition loose body meets the following conditions: the density of the core layer, the core-clad bonding layer, the cladding layer 1 and the cladding layer 2 are respectively expressed as ρ 芯层 , 芯包结合层 , 包层一 , 包层二 , ρ 芯层 < 包层一 , ρ 芯层 ≥ρ 包层二 , ρ max ﹣ρ 芯包结合层 ﹤ρ max ﹣ρ 包层一 , where ρ max is the maximum sedimentary density of the sedimentary loose body; (2) forming a core rod by sintering, degassing and stretching the deposited loose body; (3) preparing a depressed cladding outside the core rod, preparing an outer cladding outside the depressed cladding, and then sintering to form an optical fiber preform; (4) The optical fiber preform obtained in step (3) is drawn into the attenuation-stable high-element-doped optical fiber.

Citation Information

Patent Citations

  • Optical fiber preform cladding fluorine doping method

    CN103224325A

  • Single-mode optical fiber and manufacturing method thereof

    CN110221383A

  • Single-mode fiber and fabrication method thereof

    CN110794509A

  • Method for manufacturing optical fiber preform, optical fiber preform, and optical fiber

    CN114057388A

  • Optical fiber

    CN209514124U